Pengaruh Dukungan Organisasi, Disiplin Kerja Dan Work Family Conflict Terhadap Kinerja Karyawan Di CV.Suara Hati Elektronik Leneng Praya Lombok Tengah - Abdul Awwal; Siti Asiyah; Kartika Rose Rachmadi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine and analyze the effect of organizational support, work discipline, and work family conflict on employee performance at CV.Suara Hati Elektronik Leneng Praya, Central Lombok. And using saturated sampling technique. The number of samples used in this study were all employees of CV.Suara Hati, totaling 65 respondents. Data analysis methods used in this study were validity and reliability tests, normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests (Adjusted r2). Process analysis using SPSS. The results showed that organizational support, work discipline, and work family conflict simultaneously had an effect on employee performance and partially organizational support, work discipline, and work family conflict had a significant effect on employee performance. Keywords: Organizational Support, Work Discipline, Work Family Conflict